The Influence of Environmental Attitudes and Environmental Concerns on Green Purchasing Behavior with Gender as a Moderator Variable - Zahara, Rita (Siber Journal of Advanced Multidisciplinary, 2024)
The purpose of this study is to analyze the effect of environmental attitudes and environmental concerns on green purchasing behavior with gender as a moderator variable. This study also aims to analyze the effect of environmental attitudes and environmental concerns on green purchasing behavior. This research takes respondents, namely students who are under 25 years old. The number of respondents in this study amounted to 175 respondents. The sampling technique is purposive sampling. The questionnaire was distributed through online media. The results of the regression analysis show that environmental attitudes and environmental concerns affect green purchasing behavior while gender does not moderate the influence of environmental attitudes and environmental concerns on green purchasing behavior.